Criminal procedures and cross-border cooperation in the EU area of criminal justice together but apart? - Sellier, Élodie (European Studies, 2020)
This book examines to what extent differences between national and procedural criminal laws hinder the negotiations and the operation of cross-border cooperation instruments. It is based on a comparative analysis of a representative sample of Member States.